Confronting / Defining the Self : Formation and Dissolution of the 'I' from La Fayette to Grass - McCarthy, John, (Internationale Forschungen zur Allgemeinen und Vergleichenden Literaturwissenschaft ;, 2024)
Early 20th-century literary critics Joseph Collins, Hermann Hesse, and Percy Lubbock concluded that the pages of a book present a succession of moments that the reader visualizes and reinterprets. They feared that few would actually commit thems